Additive manufacturing technology: Designing new business models - Matos, F.; Godina, R.; Espadinha-Cruz, P.; Matos, M. F. (Proceedings of the 17th European Conference on Management, Leadership and Governance, ECMLG 2021, 2021)
Today’s business setting is becoming increasingly dynamic and characterised by various technological advancements. Knowledge, as well as how it is shared and preserved inside the organisations, has become a volatile active source of competitive advantage. As a result, instruments to assist organisations in managing their knowledge and leveraging value generation are required. Knowledge management processes are even more critical for companies that use or can use Additive Manufacturing Technology (AM), which is frequently linked to 3D printing, because they are in a disruptive and emergent industry, which utilises innovative and complex products, whose business models’ dynamic is still unknown. Although the tremendous potential that is presented by this technology, there are still many concerns about its future advancements and implications on society and business models. This paper aims to answer the question: What are the impacts of the adoption of AM technology on companies’ business models? Moreover, to answer the question of what knowledge management strategies can be adopted to increase the competitiveness and sustainability in the business models, in companies using AM technology? To achieve the objectives, a literature review was performed. The results demonstrated that the disruptions created by technology are not yet known to many companies. Similarly, knowledge of the impacts on business models and other elements of sustainability is limited. In terms of originality, the goal of this research is to contribute to and encourage data-driven debates about the potential implications of AM adoption on knowledge management strategies.